-0.2×3-0.7×2+4x-4

Replace the variable x with 0 in the expression.

f(0)=-0.2(0)3-0.7(0)2+4(0)-4

Simplify the result.

Simplify each term.

Raising 0 to any positive power yields 0.

f(0)=-0.2⋅0-0.7(0)2+4(0)-4

Multiply -0.2 by 0.

f(0)=0-0.7(0)2+4(0)-4

Raising 0 to any positive power yields 0.

f(0)=0-0.7⋅0+4(0)-4

Multiply -0.7 by 0.

f(0)=0+0+4(0)-4

Multiply 4 by 0.

f(0)=0+0+0-4

f(0)=0+0+0-4

Simplify by adding zeros.

Add 0 and 0.

f(0)=0+0-4

Add 0 and 0.

f(0)=0-4

Subtract 4 from 0.

f(0)=-4

f(0)=-4

The final answer is -4.

-4

-4

Convert -4 to decimal.

y=-4

y=-4

Replace the variable x with -2 in the expression.

f(-2)=-0.2(-2)3-0.7(-2)2+4(-2)-4

Simplify the result.

Simplify each term.

Raise -2 to the power of 3.

f(-2)=-0.2⋅-8-0.7(-2)2+4(-2)-4

Multiply -0.2 by -8.

f(-2)=1.6-0.7(-2)2+4(-2)-4

Raise -2 to the power of 2.

f(-2)=1.6-0.7⋅4+4(-2)-4

Multiply -0.7 by 4.

f(-2)=1.6-2.8+4(-2)-4

Multiply 4 by -2.

f(-2)=1.6-2.8-8-4

f(-2)=1.6-2.8-8-4

Simplify by subtracting numbers.

Subtract 2.8 from 1.6.

f(-2)=-1.2-8-4

Subtract 8 from -1.2.

f(-2)=-9.2-4

Subtract 4 from -9.2.

f(-2)=-13.2

f(-2)=-13.2

The final answer is -13.2.

-13.2

-13.2

-13.2

Replace the variable x with -1 in the expression.

f(-1)=-0.2(-1)3-0.7(-1)2+4(-1)-4

Simplify the result.

Simplify each term.

Raise -1 to the power of 3.

f(-1)=-0.2⋅-1-0.7(-1)2+4(-1)-4

Multiply -0.2 by -1.

f(-1)=0.2-0.7(-1)2+4(-1)-4

Raise -1 to the power of 2.

f(-1)=0.2-0.7⋅1+4(-1)-4

Multiply -0.7 by 1.

f(-1)=0.2-0.7+4(-1)-4

Multiply 4 by -1.

f(-1)=0.2-0.7-4-4

f(-1)=0.2-0.7-4-4

Simplify by subtracting numbers.

Subtract 0.7 from 0.2.

f(-1)=-0.5-4-4

Subtract 4 from -0.5.

f(-1)=-4.5-4

Subtract 4 from -4.5.

f(-1)=-8.5

f(-1)=-8.5

The final answer is -8.5.

-8.5

-8.5

-8.5

Replace the variable x with 1 in the expression.

f(1)=-0.2(1)3-0.7(1)2+4(1)-4

Simplify the result.

Simplify each term.

One to any power is one.

f(1)=-0.2⋅1-0.7(1)2+4(1)-4

Multiply -0.2 by 1.

f(1)=-0.2-0.7(1)2+4(1)-4

One to any power is one.

f(1)=-0.2-0.7⋅1+4(1)-4

Multiply -0.7 by 1.

f(1)=-0.2-0.7+4(1)-4

Multiply 4 by 1.

f(1)=-0.2-0.7+4-4

f(1)=-0.2-0.7+4-4

Simplify by adding and subtracting.

Subtract 0.7 from -0.2.

f(1)=-0.9+4-4

Add -0.9 and 4.

f(1)=3.1-4

Subtract 4 from 3.1.

f(1)=-0.9

f(1)=-0.9

The final answer is -0.9.

-0.9

-0.9

-0.9

Replace the variable x with 2 in the expression.

f(2)=-0.2(2)3-0.7(2)2+4(2)-4

Simplify the result.

Simplify each term.

Raise 2 to the power of 3.

f(2)=-0.2⋅8-0.7(2)2+4(2)-4

Multiply -0.2 by 8.

f(2)=-1.6-0.7(2)2+4(2)-4

Raise 2 to the power of 2.

f(2)=-1.6-0.7⋅4+4(2)-4

Multiply -0.7 by 4.

f(2)=-1.6-2.8+4(2)-4

Multiply 4 by 2.

f(2)=-1.6-2.8+8-4

f(2)=-1.6-2.8+8-4

Simplify by adding and subtracting.

Subtract 2.8 from -1.6.

f(2)=-4.4+8-4

Add -4.4 and 8.

f(2)=3.6-4

Subtract 4 from 3.6.

f(2)=-0.4

f(2)=-0.4

The final answer is -0.4.

-0.4

-0.4

-0.4

The cubic function can be graphed using the function behavior and the points.

xy-2-13.2-1-8.50-41-0.92-0.4

The cubic function can be graphed using the function behavior and the selected points.

Rises to the left and falls to the right

xy-2-13.2-1-8.50-41-0.92-0.4

Graph -0.2x^3-0.7x^2+4x-4